تحليل مقارن بين القاموس الكبير للعربية (KABA عربي-إندونيسي) بقلم طه حسين المجاهد و أ.عطاء الله فطاني و قاموس المنوّر (إندونيسي- عربي) لأحمد وارسون منوّر و محمد فيروس - Akhi rudin; Kasmantoni Kasmantoni (IAIN Bengkulu, 2021)
The dictionary is a tool that man generally uses to facilitate his understanding of the meaning of a particular word, whether in Arabic, English or any language in the world. Because dictionary function is a tool to help other people know the meaning of language, it is also appropriate that the dictionary is prepared in a systematic way that is easy to understand and easy for users to use a dictionary. As Tawfiq al-Rahman mentioned, the full dictionary is a dictionary that contains all words in a particular language and is equipped with an explanation of its meaning and derivation and the technique of expression and arguments (evidence) that explain the use of the word. From this point of view we can understand that the dictionary created or designed must contain criteria that can make it easier for users to find the meaning of words and facilitate their use on users.This research is qualitative research according to the study issue of this thesis, then this type of research belongs to the category of literary research (library research), that is, first, by recording all the results related to the driving of consumption in general in each research discussion found in literature and sources, and/or other discoveries on consumption-driven behavior that can affect the cycle of supply and demand. After taking notes, secondly, mix any results, whether they are theory or new results about consumer behavior III, analyze all the results from different readings, related to the absence of each source or feature or relationship about the speech discussed in it. The last is criticism, giving ideas. Similarities between the previous two dictionaries, the KABA and MUNAWWIR dictionary, are located in the writing system and dictionary type. The writing system that uses the principle of orderly (serial) alphabets makes these dictionaries equal to each other. It is also about the type of dictionary that is a kind of verbal dictionary in terms of the differences between these two dictionaries, namely kaba dictionary (great dictionary of Arabic) and munawwir dictionary is largely, but in short the researcher can state that the writing of the KABA dictionary almost reaches the complete and perfect dictionary method, while the MUNAWWIR dictionary is so far from perfect that it is not worthy as the perfect dictionary in terms of rules. But it is still very biased to use for those who know the basic rules of Arabic.